PERAN STRATEGI PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA - Savitri, Aini Shifana; Sallamah, Dewi; Permatasari, Nikie Ailsa; Prihantini, Prihantini (Universitas Tanjungpura, 2022)
Learning activities will be successful if students have motivation in learning. Therefore, the article that we created aims to better recognize and examine the effect of learning strategies applied by teachers in increasing students' learning motivation. In achieving the goal of increasing student motivation, there needs to be a better effort in choosing and implementing learning strategies that are in accordance with the competencies to be achieved. The research we conducted used a descriptive analysis approach through data collection methods. The data collection is done by studying literature through articles, journals and books. To increase students' learning motivation, it is necessary to choose the right learning strategy by considering the characteristics of the objectives and content of the field of study. The results of the analysis show that there is a big influence given by the learning strategy on increasing students' learning motivation. This influence has an impact on student learning outcomes for the better. Each learning strategy has a different effect on students' learning motivation. The application of correct learning strategies also increases students' understanding of the learning content.